Estimation of Volatile Organic Compounds (VOCs) and Human Health Risk Assessment of Simulated Indoor Environment Consisting of Upholstered Furniture Made of Commercially Available Foams - Alena Capíková; Daniela Tesařová; Josef Hlavaty; Adam Ekielski; Pawan Kumar Mishra (Advances in Polymer Technology)
This study was conducted for the qualitative and quantitative determination of volatile organic compounds (VOCs) and total volatile organic compounds (TVOC) from polymeric foam materials used in upholstered furniture. Six different types of foams viz. Highly elastic foam K5040, standard PU foam N5063, bonded polyurethane foam R100, viscoelastic foam V5020, self-extinguishing foam KF5560, and foam rubber were used. Short-term and long-term (24, 48, 72, 672 hours (28 day)) measurements were done to differentiate the role of primary emissions (present in new products) and secondary emissions (due to chemical reactions in material or slowly released due to the porous structure of material). The samples were collected using a small-space sampling chamber at a temperature of 23°C and a humidity of 50% depending on the aspect of time. The concentrations of VOC and TVOC were identified and quantified using a Gas chromatography–Mass spectroscopy (GC-MS) based method. Based on the VOC measurements, the standard room concentrations were simulated to estimate the human health risk assessment for all six types of foams. The results of simulations suggest no possibility of human health risk for the very long period (28 days), as the estimated values were found to be much below the prescribed limits.